Criticism and Hadis Explanation on Ability to Fight Invaders in MUI Fatwa No 83 of 2023 - Fatichatus Sadiyah (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2025)
Purpose: Since October 7, 2023, Israel has launched intense aggression against Palestine, resulting in over 11,200 Palestinian deaths by November 12, 2023. In response, the Indonesian Ulema Council (MUI) issued Fatwa Number 83 of 2023, concerning the law on supporting the Palestinian struggle. One of the arguments cited in the fatwa is a hadith that permits fighting invaders. This study aims to analyze the authenticity (sanad and matan) and interpretation (sharh) of this hadith while exploring its relevance to the Palestinian resistance against the Israeli occupation. Methodology: This study uses a normative approach by applying descriptive-analytical methods. Descriptive-analytical is meant here by applying the takhri>j al-h{adi>th method. Results: The analyzed hadith narrates the duel (mubarazah) between Muslim and non-Muslim warriors before the Battle of Badr. The Prophet Muhammad (SAW) permitted Ali, Hamzah, and Ubaydah to accept the challenge, resulting in victory. The hadith is authentic and highlights that dueling and armed resistance are permissible when one possesses sufficient skill and strength. Conclusion: According to Islamic law, it is lawful to fight oppressors, and helping others in such efforts—materially or immaterially—is permitted. This supports the MUI’s position that resistance to Israeli aggression is religiously justified. Limitations: This study is limited to one hadith from the MUI fatwa. A broader analysis can be performed using other hadiths or interdisciplinary perspectives. Contribution: This article highlights the content of the MUI fatwa on the permissibility of fighting against invaders in terms of hadith studies using the takhrij method.